Peuples - Quentin Bouvier (Vernacular: New Connections in Language, Literature, & Culture, 2020)
Five poems about the experience and life in a Parisian banlieue. In a country where racial tensions are occurring, it is essential to put the emphasis on the beauty of plurality.
Keywords: Poetry; France; Banlieue; Immigration Politics; Identity